First Czechoslovakian Republic versus Hungarian Kingdom: Ungvár, November 9, 1918. and Ungvár, May 8, 1919 - Gulyás, László (Acta Scientiarum Socialium, 2018)
The collapse of the Austro-Hungarian Empire began in October of 1918, raising a number of territorial questions from Bukovina to Fiume. One of these was the issue of Subcarpathia/Kárpátalja. During the autumn of 1918, many states - the forming Czechoslovakia and Poland, the various competing Ukrainian state formations – were aiming to get hold of Kárpátalja. At the same time, Hungarian politicians worked to keep the region within the Hungarian state. On November 6, 1918 in Ungvár, the Ruthenian population made a decision that was definitely favourable for the Hungarian cause. Our paper presents this decision, its background and consequences.
Keywords: Great War (1914‒1918); history of Central-Europe; birth of the First Czechoslovakian Republic; activity of Ruthenians at 1918‒1919